Analisis Faktor-Faktor yang Berpengaruh terhadap Tingkat Keberhasilan pada Perusahaan-Perusahaan Dagang di Kotamadya Banjarmasin - Rudiansyah, Muhammad (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2017)
This research is aimed to analize to factors that success of business. The factors analize in the research are; X1 (net selling), X2 (cost expense), X3 (working capital), X4 (gross profit), X5 (profit margin), X6 (total assets), dan X7 (turnover assets). The analysis tool that is used in the research is the multiple linier regression model, regression equations that show the variables X1 , X2 , X3 , X4 , X5 , X6 simultaneously give sinigficant afferst to variable Y. This is show in the test F result calculation (2,897) is higher than the table F (2,17), and its probability value (1.778E-9) is lower the value of alfa ( ? = 0,05) While the dominant factor that affects sucsess of business is the profit margin (X5).Key words; net selling, cost expense, working capita), gross profit, profit margin, total assets, turnover assets.